2013
DOI: 10.1128/iai.01087-13
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Infection Promotes Vascular Smooth Muscle Cell Migration through a Toll-Like Receptor 2-Related Signaling Pathway

Abstract: The migration of vascular smooth muscle cells (VSMCs) from the media to the intima is proposed to be a key event in the development of atherosclerosis. Recently, we reported that Chlamydia pneumoniae infection is involved in VSMC migration. However, the exact mechanisms for C. pneumoniae infection-induced VSMC migration are not yet well elucidated. In this study, we examined the role of the Toll-like receptor 2 (TLR2) activation-related signaling pathway in VSMC migration induced by C. pneumoniae infection. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In the vasculature, activated TLR signaling increases VSMC phenotypic switching, proliferation, and migration, which are essential processes in neointima formation 12, 13, 27. This evidence suggests that targeting TLR signaling may be a novel therapeutic target for treating neointima formation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the vasculature, activated TLR signaling increases VSMC phenotypic switching, proliferation, and migration, which are essential processes in neointima formation 12, 13, 27. This evidence suggests that targeting TLR signaling may be a novel therapeutic target for treating neointima formation.…”
Section: Discussionmentioning
confidence: 96%
“…Tollip can physically associate with TLR2 and TLR4 to suppress TLR signaling 11. TLR2 participates in Chlamydia pneumoniae infection–mediated VSMC migration 12. In addition, Graaf and colleagues demonstrated that heat shock protein 60–induced activation of TLR2 and TLR4 could contribute to VSMC proliferation 13.…”
Section: Introductionmentioning
confidence: 99%
“… 31 TLR2 and TLR4 may play a role in C pneumoniae -induced foam cell formation and VSMC migration. 32 34 Therefore, TLR4 and TLR2 are important candidate genes for ACI.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrate that C. pneumonia –infected rat vascular SMCs enhanced migration in a TLR2-dependent manner. 67 Rabbit-infected vascular SMCs show enhanced proliferation in response to C. pneumoniae through hsp60 and the extracellular regulated kinase-1 and −2 pathways; this is further enhanced in the presence of oxLDL. 44,51 Furthermore, in vitro studies with human vascular SMCs show that C. pneumoniae EBs induce hsp60, and this activates TLR4-mediated p44/p42 MAPK activation and SMC proliferation.…”
Section: Diseasesmentioning
confidence: 99%